Denitrification by Chromobacterium violaceum - Bazylinski, Dennis A. (1986)
One host (Rana catesbiana)-associated and two free-living mesophilic strains of bacteria with violet pigmentation and biochemical characteristics of Chromobacterium violaceum were isolated from freshwater habitats. Cells of each freshly isolated strain and of strain ATCC 12472 (the neotype strain) grew anaerobically with glucose as the sole carbon and energy source. The major fermentation products of cells grown in Trypticase soy broth (BBL Microbiology Systems, Cockeysville, Md.) supplemented with glucose included acetate, small amounts of propionate, lactate, and pyruvate. The final cell yield and culture growth rate of each strain cultured anaerobically in this medium increased approximately twofold with the addition of 2 mM NaNO(3). Final growth yields increased in direct proportion to the quantity of added NaNO(3) over the range of 0.5 to 5 mM. Each strain reduced NO(3)(−), producing NO(2)(−), NO, and N(2)O. NO(2)(−) accumulated transiently. With 2 mM NaNO(3) in the medium, N(2)O made up 85 to 98% of the N product recovered with each strain. N-oxides were recovered in the same quantity and distribution whether 0.01 atm (ca. 1 kPa) of C(2)H(2) (added to block N(2)O reduction) was present or not. Neither N(2) production nor gas accumulation was detected during NO(3)(−) reduction by growing cells. Cell growth in media containing 0.5 to 5 mM NaNO(2) in lieu of NaNO(3) was delayed, and although N(2)O was produced by the end of growth, NO(2)(−) -containing media did not support growth to an extent greater than did medium lacking NO(3)(−) or NO(2)(−). The data indicate that C. violaceum cells ferment glucose or denitrify, terminating denitrification with the production of N(2)O, and that NO(2)(−) reduction to N(2)O is not coupled to growth but may serve as a detoxification mechanism. No strain detectably fixed N(2) (reduced C(2)H(2)).